Determinants of Profitability in BCA Syariah: The Role of NPF, FDR, and DER from 2015-2023 - Permatasari, Diah; Wisandani, Iwan; Andani, Listia; Mustika Sari, Feni (Sekolah Tinggi Ekonomi Syariah Manna Wa Salwa, 2025)
Islamic banking in Indonesia has shown consistent growth, making profitability a crucial indicator of financial health and competitiveness. This study examines the effect of non-performing financing (NPF), financing-to-deposit ratio (FDR), and debt-to-equity ratio (DER) on return on equity (ROE) at BCA Syariah during 2015–2023. Using a quantitative associative design, we obtained 36 annual observations from financial statements and applied panel regression to evaluate both simultaneous and partial effects. The results indicate that NPF, FDR, and DER jointly influence ROE. Partially, NPF exerts no significant effect, FDR has a significant negative impact, while DER shows a positive but insignificant relationship with ROE. The dominance of FDR highlights the central role of liquidity management compared to credit risk and capital structure.The novelty of this study lies in its contrast with prior findings, where NPF is typically found to significantly reduce profitability. In BCA Syariah’s case, strong risk management and stable financing quality appear to mitigate the adverse effects of NPF, making liquidity pressure (FDR) the primary determinant of profitability. Theoretically, this extends the literature on Islamic banking profitability by showing that the impact of financing risk may be context-specific and shaped by internal bank governance. Practically, the findings suggest that BCA Syariah should continue improving financing quality while prioritizing stricter management of third-party funds, thereby strengthening profitability and enhancing its competitive position in the Islamic banking sector.